2017
DOI: 10.1103/physrevb.95.014106
|View full text |Cite
|
Sign up to set email alerts
|

Strain effects on the behavior of isolated and paired sulfur vacancy defects in monolayer MoS2

Abstract: We investigate the behavior of sulfur vacancy defects, the most abundant type of intrinsic defect in monolayer MoS2, using first-principles calculations based on density functional theory. We consider the dependence of the isolated defect formation energy on the charge state and on uniaxial tensile and compressive strain up to 5%. We also consider the possibility of defect clustering by examining the formation energies of pairs of vacancies at various relative positions, and their dependence on charge state an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…Even though the differences are rather small (−0.06 eV, −0.10 eV and −0.04 eV), already the observation that the energetic cost of forming divacancies is approximately equal to forming monovacancies can intuitively be regarded as rather surprising. Nevertheless, this behavior is in line with results reported by Le et al 63 as well as Sensoy et al 64 . In the latter work it is shown that the defect-induced lattice reorganization in the 2H-MoS 2 basal plane is very small and local, and that the interaction between isolated monovacancies is negligible.…”
Section: Formation Energysupporting
confidence: 82%
“…Even though the differences are rather small (−0.06 eV, −0.10 eV and −0.04 eV), already the observation that the energetic cost of forming divacancies is approximately equal to forming monovacancies can intuitively be regarded as rather surprising. Nevertheless, this behavior is in line with results reported by Le et al 63 as well as Sensoy et al 64 . In the latter work it is shown that the defect-induced lattice reorganization in the 2H-MoS 2 basal plane is very small and local, and that the interaction between isolated monovacancies is negligible.…”
Section: Formation Energysupporting
confidence: 82%
“…In this work, we simulate the Young's modulus of monolayer TX 2 cells and investigate the band structures of hexagonal and orthorhombic monolayer TX 2 cells under a wide range of strain amplitudes in different directions using first-principles methods. This theoretical method has been used in many previous studies in TMDs [23][24][25][26][27]. Our aim is to theoretically explore the relationship between the Young's modulus and the width of the direct band gap region.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In particular, the scheme proposed by Freysoldt, Neugebauer and Van de Walle (FNV) has gained a lot of popularity owing to its consistency in deriving accurate corrections for charged defects in numerous materials [26]. This scheme has been extended to low-dimensional systems as well, and shown to perform well [38,39,40,41,42,43,44]. However, a generalized correction scheme implementation that works with bulk as well as low-dimensional systems is absent in the various DFT packages, or as an independent package [45,46].…”
Section: Introductionmentioning
confidence: 99%